1987
DOI: 10.3109/00365598709180280
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Sperm Antibodies in Adult Rats after Prefertile Traumatic vas Lesions

Abstract: The occurrence of sperm antibodies has been studied in adult rats, which at prefertile age had been subjected to unilateral vasectomy, unilateral or bilateral crush injury of the vas or bilateral resection of the ductal artery. By means of indirect immunofluorescence technique, circulating sperm antibodies could be demonstrated in the blood in all groups 13 weeks postoperatively: unilateral vasectomy 15/17 (88%), unilateral crush injury 14/20 (70%), bilateral crush injury 13/20 (65%) and vascular injury 14/20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The operative field remains hazardous despite measures that are claimed to reduce the inflammatory response (Corkery, 1975). The vas and testicular vessels may be visibly or covertly damaged, only to present later as gonadal atrophy or infertility (Janik and Shandling, 1982;Pedersen et al, 1987;Parkhouse and Hendry, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The operative field remains hazardous despite measures that are claimed to reduce the inflammatory response (Corkery, 1975). The vas and testicular vessels may be visibly or covertly damaged, only to present later as gonadal atrophy or infertility (Janik and Shandling, 1982;Pedersen et al, 1987;Parkhouse and Hendry, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of contralateral testicular damage after unilateral vas ligation has been demonstrated to be mediated through antisperm autoantibodies in several studies (Haas, 1987;Pedersen et al, 1987;Flickinger et al, 1988;Chehval et al, 1995). It has been reported that early repair of the severed vas, before the development of antisperm autoantibodies, will avoid potential damage to the contralateral testicle (Flickinger et al, 2000).…”
mentioning
confidence: 99%
“…There is some evidence that experimental injury to the vas deferens before puberty in rats is Read at the 46th Annual Meeting of the British Association of Urological Surgeons in Scarborough, July 1990 associated with later production of antibodies to spermatozoa and that early vasal reconstruction prevents this phenomenon (Pederson et al, 1987). However, there have been no detailed studies in humans to ascertain whether vasal injuries in childhood are of relevance to later fertility.…”
mentioning
confidence: 99%